Analysis of the Interference Effects in CMOS Image Sensors Caused by Strong Electromagnetic Pulses - Zhikang Yang; Lin Wen; Yudong Li; Dong Zhou; Xin Wang; Rui Ding; Meiqing Zhong; Cui Meng; Wenxiao Fang; Qi Guo (Journal of Electromagnetic Engineering and Science, 2024)
With the electromagnetic environment becoming increasingly complex, it is crucial to address the risk posed by electromagnetic pulse, which critically impairs the performance and reliability of electronic systems based on complementary metal oxide semiconductor (CMOS) image sensors. In this context, research on the failure types of CMOS image sensors in a high-power electromagnetic environment, caused by strong electromagnetic pulses and the rapid evaluation method of interference immunity, has garnered significant interest. This paper conducts electromagnetic pulse simulation experiments on CMOS image sensors to first study their failure types, such as image abnormalities and functional interruption, and then identify the corresponding failure criteria. Furthermore, this study builds on the small sample test evaluation method to investigate the interference threshold of functional interruptions in CMOS image sensors by calculating the failure probability at different field strengths. The obtained data were combined with the Weibull distribution function for fitting, the results of which found the interference threshold to be at 40.4 kV/m. The findings of this study provide a basis for evaluating the survivability of CMOS image sensors and their associated reinforcement technology in high-power electromagnetic environments.